Relationships between radial glial progenitors and 5-HT neurons in the paraventricular organ of adult zebrafish – potential effects of serotonin on adult neurogenesis - Pérez, María Rita (2013)
In non-mammalian vertebrates, serotonin (5-HT)-producing neurons exist in the paraventricular organ (PVO), a diencephalic structure containing cerebrospinal fluid (CSF)-contacting neurons exhibiting 5-HT or dopamine (DA) immunoreactivity. Because the brain of the adult teleost is known for its neurogenic activity supported, for a large part, by radial glial progenitors, this study addresses the origin of newborn 5-HT neurons in the hypothalamus of adult zebrafish. In this species, the PVO exhibits numerous radial glial cells (RGCs) whose somata are located at a certain distance from the ventricle. To study relationships between RGCs and 5-HT CSF-contacting neurons, we performed 5-HT immunohistochemistry in transgenic tg(cyp19a1b-GFP) zebrafish in which RGCs are labelled with GFP under the control of the cyp19a1b promoter. We show that the somata of the 5-HT neurons are located closer to the ventricle than those of RGCs. RGCs extend towards the ventricle cytoplasmic processes that form a continuous barrier along the ventricular surface. In turn, 5-HT neurons contact the CSF via processes that cross this barrier through small pores. Further experiments using proliferating cell nuclear antigen or 5-bromo-2′-deoxyuridine indicate that RGCs proliferate and give birth to 5-HT neurons migrating centripetally instead of centrifugally as in other brain regions. Furthermore, treatment of adult zebrafish with tryptophan hydroxylase inhibitor causes a significant decrease in the number of proliferating cells in the PVO, but not in the mediobasal hypothalamus. These data point to the PVO as an intriguing region in which 5-HT appears to promote genesis of 5-HT neurons that accumulate along the brain ventricles and contact the CSF.